2021
DOI: 10.1186/s12873-021-00451-1
|View full text |Cite
|
Sign up to set email alerts
|

Tidal volume according to the 4-point sealing forces of a bag-valve-mask: an adult respiratory arrest simulator-based prospective, descriptive study

Abstract: Background For adequate ventilation during bag-valve-mask ventilation, rescuers should ensure a proper mask seal using the one-handed or two-handed technique. Little is known about the magnitude of sealing forces of a bag-valve-mask needed for adequate ventilation. This study aimed to explore the effect of the 4-point sealing forces of a bag-valve-mask on tidal volume while using the one-handed technique, focusing on the moderating effect of C length (the distance from the thumb to the index fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 20 publications
2
6
1
Order By: Relevance
“…Among the 4-spot adhesion strengths, the force at the bottom contact point was lower than that measured at the right and left of the mask. However, the bottom sealing force was the highest and that the apex sealing force was the weakest, which was in line with the results of Uhm and Kim [ 24 ]. Given the paucity of investigations that analyzed the 4-spot adhesion strength between the mask and face, it was difficult to explain the disparities between the findings.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Among the 4-spot adhesion strengths, the force at the bottom contact point was lower than that measured at the right and left of the mask. However, the bottom sealing force was the highest and that the apex sealing force was the weakest, which was in line with the results of Uhm and Kim [ 24 ]. Given the paucity of investigations that analyzed the 4-spot adhesion strength between the mask and face, it was difficult to explain the disparities between the findings.…”
Section: Discussionsupporting
confidence: 90%
“…This was the result of controlling for gender, grade, and orientation of the hand that sealed the mask. This result is in the same context as a study that emphasized a higher sealing force between the thumb and index finger compared to the existing EC technique [ 11 ] and a study that the ventilation increased as the distance between the thumb and index finger increased [ 20 , 24 ]. However, to accurately identify the cause of these results, follow-up studies are needed.…”
Section: Discussionsupporting
confidence: 70%
“…Although previous studies have reported that the factors affecting effective ventilation were sex, height, weight, C length in the E–C technique, handgrip power, hand width, hand length 11 , 16 , 17 , it is difficult to confirm which factors affect BVM ventilation, especially because few follow-up studies use the same variables. Nevertheless, the rescuer’s hand function is important for appropriate ventilation because BVM bagging with the E–C technique requires the hands 11 , 18 .…”
mentioning
confidence: 98%
“…To provide appropriate ventilation without side effects, the mask in BVM was improved so that the entire mask could be controlled with one hand by making a power grip on the mask apex to seal the mask to the face well 13 , and the BVM was modified by adding a supplemental internal handle 12 and external handle 14 or using the pediatric BVM for adults 15 . In addition, a study measuring the 4-spot adhesion strength (sealing forces measured at the bottom, left side, right side and apex of the mask) between a mask and a manikin’s face using the E–C technique demonstrated that the tidal volume (Vt) increases when the apex sealing force during BVM ventilation increases 16 . However, it is difficult to apply more force to the apex of the mask when using a one-handed E–C technique for ventilating the patient; therefore, it is necessary to consider shifting the center of gravity to the apex of the mask.…”
mentioning
confidence: 99%
See 1 more Smart Citation